Analysis of Learning Media Use in SD Negeri Bangunjiwo - Septikasari, Zela; Devinda, Devinda; Perwitasari, Ningrum (Fakultas Keguruan dan Ilmu Pendidikan, Universitas Mataram, 2025)
The success of the learning process is largely determined by the teacher's ability to deliver material and use learning media. Good learning media depends on the availability of facilities and infrastructure in schools, teacher creativity, teacher capacity building, and funding support in making learning media. This study aims to analyze (1) The use of learning media at SD Negeri Bangunjiwo, (2) The obstacles faced by teachers and students during learning using learning media. This research is a descriptive qualitative research using interview and observation data collection techniques. Respondents in this study were the Principal, Low Grade Teacher and Low Grade Students. The results showed that (1) teachers prepare learning media tailored to students' learning styles, (2) obstacles faced when using media are funds, facilities and infrastructure that are less supportive, and different students' knowledge related to learning media. The conclusion of the research is that the use of learning media is proven to improve student learning outcomes. Support from external school parties is needed in providing learning media that can maximize learning activities at school.